Diminished nitroprusside-induced relaxation of inflamed colonic smooth muscle in mice - J. D. van Bergeijk; H. van Westreenen; P. Adhien; F. J. Zijlstra (Mediators of Inflammation)
The dextran sodium sulphate (DSS) induced colitis in mice was used as a experimental model to study the contractility of murine longitudinal colonic smooth muscle during inflammation. Smooth muscle segments of proximal, middle and distal colon were mounted in organ baths . Smooth muscle contraction was induced by carbachol, showing an aboral increase in activity, where as in the inflamed middle colonics egment a marked decr ease in activity was observed. The dilatative effect of sodium-nitroprus -side (SNP) as a nitric oxide donor was investigated after precontraction by carbachol. Both in normal and DSS segments administration of SNP to isolated mouse colonic smooth muscle preparations caused regional differences in relaxation, the highest relaxation seen in normal proximal colonic tissue. However, this relaxation was markedly reduced in inflamed proximal preparations , associated with a diminished cGMP contents .